The evaluation of the learning in the faculty of Education of the University of the Quindío: a look from the cognitive issue (Revista de Investigaciones Universidad del Quindío, 2013)
The study has as purpose to investigate the reasoning involved in the evaluation of the learning up to coming to the evaluation as experience of learning and formation in the Faculty of Education of the University of the Quindío. The qualitative methodology with a structural approach was in use, which allowed to pass from a descriptive level of the evaluation of the learning and the reasoning involved to an explanatory and interpretive tructure of the evaluation. The population of study is the evaluation of the learning of the academic spaces (subjects, matters) of the programs of the Faculty of Education of the University of the Quindío. The findings correspond to the evaluation of the learning of twenty academic spaces. The information was gathered from two students by academic space, in the cases in which the information supplied by the students was insufficient; it was done by the teachers.The information was categorized from the triárchic theory of the intelligence by Robert J. Sternberg (1990) with regard to the uses of the knowledge, that is to say, the knowledge with an analytical, creative and practical intention. It was found that the evaluation of the learning starts from evaluating a memory knowledge, it means, a textual knowledge, up to demanding intellectual evaluations that involves three main reasoning: the analytical one, the creative one and the practical one. The analytical reasoning stimulated in the evaluation of the majority of the academic spaces, the analytical critic and the creative which are less stimulated, followed by the practical reasoning.
Keywords: learning; evaluation of the learning; reasoning